Analysis of Phonetic/Phonological Perception of the English Monophthongs at Tertiary Level - Dančetović, Nikola N. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper discusses phonological competences of students of the first and fourth year of the Department of English Language and Literature at Faculty of Philosophy in Kosovska Mitrovica. Students ability to identify relevant elements of the English vowel system (namely, monophthongs) is tested through qualitative and quantitative oppositions of monophtongs [ɪ]-[iː], [e]-[æ], [ʌ]-[ɑː], [ɒ]-[ɔː], and [ʊ]-[uː], with the aim to determine how the two-year period of studies affected the overall competence of students of the final year. The research comprised thirty respondents, who were divided into two groups. Each group consisted of ten female and five male subjects. Upon completion of the research, we started to analyze the obtained results, which were further discussed from the perspectives of the respondents, separate groups, and in the context of phonetic/phonological theories from literature.